PROFILE OF DRUG RELATED PROBLEMS (DRPS) IN OUTPATIENT HYPERTENSION PATIENTS AT BAYUNG LENCIR PUBLIC HEALTH CENTER IN 2024: HYPERTENSION - Putri Ayu; Siti Marwah Lestari (STIKes Mandala Waluya Kendari, 2026)
Background; Drug-related problems (DRPs) are events associated with drug therapy, whether actual or potential, that may hinder the achievement of intended health outcomes. This study describes the profile of DRPs occurrences among outpatient hypertensive patients at Bayung Lencir Community Health Center in 2024, based on the Pharmaceutical Care Network Europe (PCNE) classification version 9.1. Methods: A non-experimental, cross-sectional design with retrospective data collection was employed, utilizing purposive sampling. The identification and evaluation of DRP incidents were conducted based on the PCNE V9.1 classification. Results: The results show that antihypertensive drug use was predominantly from the Calcium Channel Blocker (CCB) class, particularly amlodipine (86.59%). Among the 82 patients who met the inclusion criteria, 52 experienced DRPs. The primary DRP categories identified were potential suboptimal drug treatment effects (13.89%), untreated indications or symptoms (8.33%), potential adverse drug events (72.22%), and unnecessary drug therapy (4.17%). The incidence of drug-related problems (DRPs) among outpatients with hypertension at the Bayung Lencir Community Health Center remains relatively high, with the most common category being potential adverse drug events. Conclusion: The results of this study highlight the importance of comprehensive evaluation to improve treatment effectiveness and patient safety.